Book Review: Guseva A. 2008. Into the Red: The Birth of the Credit Card Market in Postcommunist Russia. Stanford: Stanford University Press - Ольга Евгеньевна Кузина (Journal of Economic Sociology, 2010)
Detailed description in the text